Investigation of marine corrosion characteristics of 10CrNiCu steel subjected to stress fields using an improved 3D cellular automata modeling - Lin Hua; Zhiyuan Hu; Wenwei Wu; Zhiyuan Mei; Meiguang Cao; Ligang Peng; Cong Liu (Materials & Design)
The corrosion process of hull structures in marine environments involves the coupling of multiple physical fields, including electrochemistry, mechanics, and chemistry, which is quite complex. However, there is limited field test data on the corrosion behavior of commonly used steels in hull structures when influenced by stress fields. This study focuses on 10CrNiCu steel and conducts marine corrosion tests under stress conditions in the South China Sea. The surface topography is measured using a laser confocal microscope, and thorough analysis has been performed on the characteristics of steel corrosion damage and biological attachment patterns across different marine regions (non-wettable, semi-wettable, and wettable) and stress levels (elastic stress, plastic stress). Concurrently, based on actual marine corrosion data from the South China Sea, this paper proposes an improved 3D cellular automata modeling method that accounts for the effects of biological attachment, aiming to simulate the actual marine corrosion processes of steel accurately. The performance of the stress-loading device has been enhanced to ensure rapid, stable loading, and stress maintenance. By exploring the influence of stress fields on steel corrosion comprehensively, this work provides significant insights for corrosion assessment and anti-corrosion design in various marine regions. The proposed 3D cellular automata model enhances simulation accuracy by incorporating the effects of biological attachment, thereby reducing the need for extensive marine corrosion tests and offering technical support for assessing structural residual strength.